Quality Characteristics of Nutri-fried Noodles Made from Sweet Potato Tubers and Tops Ipomea batatas - de Jesus, Geraldine F.; Dicen, Shirley G.; Jarque, Maria Crisanta M. (JPAIR Multidisciplinary Research, 2016)
Noodles made from sweet potato can be a healthier alternative to commercially produced ones since it is rich in vitamins and minerals. The product has no artificial preservatives, and the sweetness of its taste comes naturally from the sugar content of the Camote tubers. The project is the second phase of a study on the development of nutri-noodles made from the tubers and tops of sweet potato.  The study determined the physicochemical and microbial analysis and shelf-life of the product and verify its acceptability through quantitative testing. The sample was submitted to Department of Science and Technology Region V for analysis and the results were: 6.53% moisture, 0.13% free fatty acids and
Keywords: Marketing; Quality; fried noodles; sweet potato; shelf-life; consumer testing; sorsogon; Philippines